A novel in vivo model of puncture-induced iris neovascularization - Beaujean, Ophélie (PLoS One, 2017)
PURPOSE: To assess iris neovascularization by uveal puncture of the mouse eye and determine the role of angiogenic factors during iris neovascularization. METHODS: Uveal punctures were performed on BalbC mouse eyes to induce iris angiogenesis. VEGF-blockage was used as an anti-angiogenic treatment, while normoxia- and hypoxia-conditioned media from retinal pigment epithelium (RPE) cells was used as an angiogenic-inducer in this model. Iris vasculature was determined in vivo by noninvasive methods. Iris blood vessels were stained for platelet endothelial cell adhesion molecule-1 and vascular sprouts were counted as markers of angiogenesis. Expression of angiogenic and inflammatory factors in the puncture-induced model were determined by qPCR and western blot. RESULTS: Punctures led to increased neovascularization and sprouting of the iris. qPCR and protein analysis showed an increase of angiogenic factors, particularly in the plasminogen-activating receptor and inflammatory systems. VEGF-blockage partly reduced iris neovascularization, and treatment with hypoxia-conditioned RPE medium led to a statistically significant increase in iris neovascularization. CONCLUSIONS: This study presents the first evidence of a puncture-induced iris angiogenesis model in the mouse. In a broader context, this novel in vivo model of neovascularization has the potential for noninvasive evaluation of angiogenesis modulating substances.